2004
DOI: 10.1002/cncr.20545
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic breast carcinoma confined to bone

Abstract: BACKGROUND The current study was performed to study metastatic breast carcinoma that remains confined to bone. METHODS The medical notes of 2514 breast carcinoma patients who were treated in 2 academic units over a 20‐year period were screened and patients who fulfilled the following criteria were selected: 1) clinical manifestation and imaging confirmation of bone metastases, and 2) metastatic disease remaining confined to bone for a minimum of 24 months. Available clinical and pathologic data were recorded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 17 publications
(15 reference statements)
0
40
0
5
Order By: Relevance
“…The number of metastatic sites and the type of metastatic tumor load also affect survival [3][4][5][6][7]. Prior reports have shown that patients with metastatic spread limited to the skeleton have a relatively prolonged survival [7][8][9][10].…”
Section: Introductionmentioning
confidence: 98%
“…The number of metastatic sites and the type of metastatic tumor load also affect survival [3][4][5][6][7]. Prior reports have shown that patients with metastatic spread limited to the skeleton have a relatively prolonged survival [7][8][9][10].…”
Section: Introductionmentioning
confidence: 98%
“…Consequences of bony metastases include pathologic fracture, spinal cord compression, anemia, and hypercalcemia [6] . Breast cancer has a particular affinity for the spine, accounting for approximately twothirds of the osseous metastases discovered [7] . Of these lesions to the spine about one-third become symptomatic, causing intractable pain, neurological deficits, mechanical instability, and ultimately disability and a severe deterioration in quality of life [8,9] .…”
Section: Topic Highlightmentioning
confidence: 99%
“…Si bien la localización de la metástasis no define si existe un peor o mejor pronóstico, debemos mencionar que existe una predominancia por tórax seguido de columna vertebral, lo cual es diferente a lo que se ha reportado en la literatura 4,9 . Sin embargo, es relevante decir que es raro encontrar metástasis en extremidad superior y cráneo.…”
Section: Discusión Y Conclusionesunclassified
“…Según la literatura, estudios realizados en 1987 han reportado una sobrevida de 24 meses, con una supervivencia a los 5 años de un 40% en pacientes portadores de metástasis óseas 3,7 . Estudios posteriores en 2002, reportaron una sobrevida media de 18 a 24 meses, con una supervivencia a los 5 años del 20% 8 , y si la metástasis está confinada sólo a esqueleto, se estimó una sobrevida promedio de 6 años 9 . El sitio más común de metástasis es la columna vertebral (63%), seguido por pelvis, esternón, costillas, cráneo y huesos largos 4,9 .…”
Section: Introductionunclassified
See 1 more Smart Citation